N-Methyl-D-Aspartate Receptor Activation Is Downstream Coupled to Pannexin 1 Opening by Src Kinase in Dorsal Horn Neurons: An Essential Link for Mechanical Hyperalgesia in Nerve-Injured Rats - Constandil-Cordova, L; Retamal-Santibanez, J; Aránguiz-Barrera, J; Renard, G; Ampuero-Llanos, E; Pelissier, T; Bravo-López, D; Hernandez-Hernandez, J (Lippincott Williams and Wilkins, 2025)
A well-recognized molecular entity involved in pain-related neuroplasticity is the N-methyl-D-Aspartate receptor (NMDAR), which is crucial for developing chronic pain. Likewise, the pannexin 1 (Panx1) channel has been described as necessary for initiating and maintaining neuropathic pain, driving nociceptive signals dependent on spinal NMDAR through several possible mechanisms. Through behavioral, pharmacological, and molecular approaches, our study in male rats has revealed several key findings: (1) neurons located in spinal cord laminae I and II express functional Panx1 channels in both neuropathic and sham rats. These channels can open (indicated by YOPRO-1 uptake) through the stimulation of NMDARs with intrathecal NMDA; (2) intrathecal NMDA leads to increased expression of pSrc and pPanx1 in dorsal horn neurons. This elevation exacerbates existing mechanical hyperalgesia in nerve-injured rats; (3) inhibition of Src with intrathecal PP2 or blockade of Panx1 with intrathecal 10Panx effectively mitigates NMDA-induced effects and reduces the spontaneous mechanical hyperalgesia of nerve-injured rats. Notably, while 10Panx successfully alleviates hyperalgesia, it does not alter pSrc expression; and (4) NMDA-stimulated YOPRO-1 uptake in neurons of laminae I-II of spinal cord slices were prevented by the NMDAR antagonist D-AP5, the Src inhibitor PP2 (but not PP3), as well as with the 10Panx and carbenoxolone. Therefore, NMDAR activation in dorsal horn neurons triggers an NMDAR-Src-Panx1 signaling pathway, where Panx1 acts as an enhancing effector in neuropathic pain. This implies that disrupting the NMDAR-Panx1 communication (eg, through Src inhibitors and/or Panx1 blockers) may offer a valuable strategy for managing some forms of chronic pain. © 2024 The Author(s).